Java Card Approach to Emulate The Indonesian National Electronic ID Smart Cards - Dwidharma Priyasta; Wahyu Cesar; Yanti Susanti; Juliati Junde (Scientific Journal of Informatics)
This paper presents a successful effort in emulating the Indonesian national electronic ID smart cards using Java Card. The aim is to provide theopportunity for other smart card products to contribute in the national electronic ID program. The life cycle status, the file system concept, commands and security procedures implemented in the Indonesian national electronic ID were reproduced and emulated ina Java Card applet. In the first stage, the emulator applet was tested using some test scenarios developed during the implementation phase. Later on, the emulator applet was tested in the real system under supervisioned by Direktorat Jenderal Kependudukan dan Pencatatan Sipil in order tomeasure its reliability as well as to determine that its behaviour is identical with the Indonesian national electronic ID. The results confirmed that this approach was fruitful.